Long-term stability of sorbed phosphorus by drinking-water treatment residuals: mechanisms and implications - Makris, Konstantinos C. (My University, 2004)
Drinking-water treatment residuals (WTRs) are amorphous metal hydroxides with significant phosphorus (P) retention capacities, and offer significant potential to costeffectively control soluble P losses in P-impacted sandy soils. The long-term stability of WTR-immobilized P, however, is unknown and is of major concern to regulatory agencies. We studied the sorption/desorption capacities, kinetics, and mechanisms involved in the reaction of P with three Fe-based and four Al-based WTRs. Three approaches to “compress” long-term effects and simulate them experimentally, were used: a) monitor the longevity of the WTR effect on soil P extractability (5.5 years after WTR application) at two sites (Holland, MI); b) study the physical nature of the WTRs, because micropores may severely restrict P desorption; and c) use heat incubations at elevated temperatures (46, 70 C) to hasten reactions that occur over decades in the field. Phosphorus sorption capacities of the WTRs were a function of oxalate-extractable Fe and Al, % C, and porosity, as expressed by the ratio of specific surface areas measured with N2 and CO2. Phosphorus desorption from the WTRs was minimal. Intraparticle diffusion in micropores of WTRs was the main mechanism of P sorption as inferred by multiple lines of solid-state and chemical assessments for two P-loaded WTRs, which is consistent with the minimum P desorption. In effect, P diffuses to the interior of particles where it is retained tenaciously. Monitoring of soil P levels with time in two WTR-amended soils showed that P extractability did not significantly increase 5.5 years after WTR application. In parallel, 2 years of heat incubation suggested that P sorbed on WTRs was not released with time, or with increasing incubation temperature. Field and heat incubation data coupled with the fact that intraparticle P diffusion in micropores was the main mechanism, were consistent with irreversible P sorption and imply that WTR-immobilized P is stable in the long term.
Keywords: Drinking-water treatment residuals (WTRs); Phosphorus sorption; Sorption/desorption capacities